Fasciola gigantica–Derived Excretory-Secretory Products Alter the Expression of mRNAs, miRNAs, lncRNAs, and circRNAs Involved in the Immune Response and Metabolism in Goat Peripheral Blood Mononuclear Cells - Wang, Sha-Sha; Chen, Dan; He, Jun-Jun; Zheng, Wen-Bin; Tian, Ai-Ling; Zhao, Guang-Hui; Elsheikha, Hany M.; Zhu, Xing-Quan (Frontiers in Immunology, 2021)
Fasciola gigantica produces excretory-secretory products (ESPs) with immune-modulating effects to promote its own survival. In this study, we performed RNA-seq to gain a comprehensive global understanding of changes in the expression of mRNAs, miRNAs, lncRNAs and circRNAs in goat peripheral blood mononuclear cells (PBMCs) treated with F. gigantica ESPs. A total of 1,544 differently expressed mRNAs (790 upregulated and 754 downregulated genes), 30 differently expressed miRNAs (24 upregulated and 6 downregulated genes), 136 differently expressed circRNAs (83 upregulated and 53 downregulated genes) and 1,194 differently expressed lncRNAs (215 upregulated and 979 downregulated genes) were identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses revealed that F. gigantica ESPs altered the expression of genes associated with the host immune response, receptor signaling, disease and metabolism. Results from by RNA-seq were validated by qRT-PCR. These findings provide an important resource for future investigation of the role of mRNAs and non-coding RNAs in mediating the immune-modulating effects of F. gigantica ESPs.